Essentiality for rice fertility and alternative splicing of OsSUT1. (January 2022) - Wang, Xiaowen; Liu, Xiuli; Hu, Zhi; Bao, Shuhui; Xia, Huihuang; Feng, Bing; Ma, Lai; Zhao, Gengmao; Zhang, Dechun; Hu, Yibing
Abstract: Sucrose-proton symporters play important roles in carbohydrate transport during plant growth and development. Their physiological functions have only been partly characterized and their regulation mechanism is largely unclear. Here we report that the knockout of a sucrose transporter gene, OsSUT1, by CRISPR-Cas9 mediated gene editing resulted in a slightly dwarf size and complete infertility of the gene's homozygous mutants. Observation of caryopsis development revealed that the endosperm of OsSUT1 mutants failed to cellularize and did not show any sign of seed-filling. Consistently, OsSUT1 was identified to express strongly in developing caryopsis of wild-type rice, particularly in the nucellar epidermis and aleurone which are critical for the uptake of nutrients into the endosperm. These results indicate that OsSUT1 is indispensable during the rice reproductive stage particularly for caryopsis development. Interestingly, OsSUT1 possesses at least 6 alternative splicing transcripts, including the 4 transcripts deposited previously and the other two identified by us. The differences among these transcripts primarily lie in their coding region of the 3′ end and 3′ UTR region. Real-time PCR showed that 4 of the 6 transcripts had different expressional patterns during rice vegetative and reproductive growth stages. Given the versatility of the gene, addressing its alternative splicing mechanism may expand our understanding of SUT's function substantially.